Health Related Quality of Life among Hypertensive Patients Attending Medical and Nephrology Clinics of Serdang Hospital, Selangor - Khaw, Wan-Fei. (2010)
It has been suggested that hypertension affects patients’ quality of life, possibly due to hypertension itself, treatment, and psychological conditions. Complication in hypertension is a major cause of morbidity and mortality, as well as deterioration in a patient’s daily life. The purpose of this study was to examine the relationship between hypertension and health-related quality of life (HRQOL) and to explore the effects of complications on people with hypertension. This study was a cross-sectional in design that involved 388 hypertensive patients receiving treatment at the medical and nephrology outpatient clinics in Serdang Hospital, Selangor. Socio-demographic data, clinical status and lifestyle behaviours were obtained from the patients. The SF-36 questionnaire was administered by interview to the participants to measure their HRQOL. The SF-36 scores of hypertensive subjects were compared with the Malaysian norm. Independent association of hypertension with each quality of life domain was analysed using multiple linear regression, so were the effects of complications on the HRQOL of hypertensive patients. Respondents scored lower than general population in six SF-36 dimensions except for bodily pain and role emotional dimensions. Out of 388 respondents, 293 (75.5%) were diagnosed as having complications. In regression models, age affected physical health domain negatively (physical functioning: β = -0.180, p < 0.01) but affected mental domains positively (vitality: β = 0.151, p < 0.05; mental health: β = 0.197, p < 0.01). Women generally scored lower in mental health than men did (β = -0.114, p < 0.05). Chinese rated significantly better in the social functioning domain (β = 0.116, p < 0.05), but Indians had significantly lower vitality score (β = -0.107, p < 0.01). Educational level affected five of the domains, especially the mental constructs. Other socio-economic variables include working status, marital status and family income had no impact on HRQOL. The presence of heart disease, diabetes mellitus, stroke, nephropathy, and visual impairment were also major determinants of the HRQOL among respondents. Healthy lifestyle behaviours such as physically active and consuming five or more servings of vegetables and fruits daily were significant positive predictors of perceived HRQOL. Older age increased participants’ likelihood of experiencing complications 1.2 times relative to younger participants (odds ratio = 1.24, Wald = 11.29, p = 0.001). Multivariate analysis of covariance, controlling for socio-demographic, clinical, and lifestyle variables, revealed that hypertensive patients with health complications scored significantly lower on physical component summary compared with hypertensive patients without health complications (p = 0.004), but no differences emerged on the mental component summary. Analysis of covariance on the subscale scores revealed that, hypertensive patients who had health complications scored significantly lower on the physical functioning (p = 0.003), role physical (p = 0.006), vitality (p = 0.008), and general health (p = 0.021). The study provides evidence for a model that links patients’ status with regard to demographic, clinical, healthy behaviours and HRQOL, which may help clinicians to increase their effectiveness in planning therapeutic interventions that will ensure desirable HRQOL as well as controlling of blood pressure. Hence, subsequent interventions can reduce complications or adverse cardiovascular events.